Online Business of Selling Prosthetics for 3D Character Makeup - Valeska Tezaiswari (Jurnal Tata Rias, 2019)
The purpose of this study is to describe: (1) the implementation of online business for the sale of prosthetics for 3D character makeup, (2) the obstacles faced by online businesses in the sale of prosthetics for 3D character makeup, and (3) sales efforts in overcoming these obstacles. The subjects of this study were sellers of prosthetics for 3D character makeup. The objects of this study were online business implementation, online business obstacles, and sellers' efforts in overcoming these obstacles. Research data was obtained through observation, interviews, and document analysis. The results show: First, the implementation of online business for the sale of prosthetics for 3D character makeup has good and profitable potential. Second, the obstacles faced include the still-unfamiliarity of many consumers with prosthetics for 3D character makeup, and the distrust of online sales due to the prevalence of fraud. Third, sellers' efforts to overcome these obstacles include online and offline promotions, such as opening booths at bazaars, soliciting testimonials from buyers, maintaining product quality, and checking current trends. Keywords: online business, prosthetics, character makeup.